2011
DOI: 10.1179/107735211799031149
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Incidence Rates of Occupational Diseases in Mongolia, 1986–2006

Abstract: The purpose of this study was to determine incidence rates and time trends of major occupational diseases in Mongolia. We retrieved information about all 4598 patients from 1986 to 2006 who were diagnosed and registered with occupational diseases by the National Center of Workplace Conditions and Occupational Diseases. There was an increasing trend for new cases as well as for incidence rates of reported occupational respiratory diseases (ORD), musculoskeletal disorders (MSD), cardiovascular diseases, skin dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…We chose the mining industry as the reference group because it is currently the leading economic industry in terms of gross domestic product in Mongolia. 31 Compared with the mining industry, participants from all other industries other than the construction industry had significantly higher depression scores, although it has the highest proportion of people with minimum depression.…”
Section: Resultsmentioning
confidence: 95%
“…We chose the mining industry as the reference group because it is currently the leading economic industry in terms of gross domestic product in Mongolia. 31 Compared with the mining industry, participants from all other industries other than the construction industry had significantly higher depression scores, although it has the highest proportion of people with minimum depression.…”
Section: Resultsmentioning
confidence: 95%
“…Tables 1 and 2 show the prevalence and levels of exposure to common environmental risk factors in Mongolia, and associations between environmental risk factors and health outcomes among adults and children are reported in Tables 3 and 4. 3-5,11,14-41,44,45,47-49,51,54,55,58,62,66-82…”
Section: Resultsmentioning
confidence: 99%
“…The retrospective-cohort studies included 47-49 found an overall increase in the annual incidence rates of occupational diseases, including chronic bronchitis, pneumoconiosis, asthma, tuberculosis, lung cancer, poisonings, and musculoskeletal and cardiovascular diseases. Oyunbileg et al 48 reported increases in the cumulative incidence rate 30-59 of occupational respiratory diseases (1.4% per year) and in the cumulative incidence rate 30-59 of musculoskeletal disorders (2.3% per year) in the period from 1986 to 2006. Actually, these increases might be more than the reported values because of underreporting of these diseases resulting from the presence of informal and/or unregistered factories, especially in the mining i...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation